HUKUM MEMBACA ALQURAN BAGI WANITA HAID PERSPEKTIF MAZHAB HANAFI DAN MAZHAB MALIKI (TINJAUAN ISTIHSAN) - Muhammad Nabih Ali (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Reading the Qur’an is one of the blessings advocated by the Prophet Muhammad, even there are virtues when reading it. Therefore the Qur'an should be read, studied and understood by Muslims, both men and women. When reading the holy book, one should read it in a holy state, both sacred from small hadas and large hadas to honor the glory of the Qur’an. Scholars differ in their opinions in reading the Qur’an for menstruating women, there are opinions that forbid and allow it. This study examines two schools namely the Hanafi school of thought and the Maliki school of reading Qur'anic law for menstruating women. The author uses the theory of istihsan with nas and istihsan with emergency in the Hanafi school and istihsan with maslahat and istihsan by rejecting the difficulties and difficulties in the Maliki school. The results showed that the Hanafi school forbids menstruating women from reading the Qur’an as a whole, but allowing menstruating women to read the Qur’an with the provisions of only reading vocabulary only and reading it intentionally besides reading, such as praying, dhikr, and praising God. As for the Maliki school of law, it is absolutely permissible for menstruating women to read the Qur’an before menstruation has gone or not and is afraid of forgetting whether or not to memorize it. In the equation, the two schools use the same argument, but different interpretations of the argument.